Mapping Forest Degradation and Contributing Factors in a Tropical Dry Forest - Jiménez-Rodríguez, Diana Laura; Gao, Yan; Solórzano, Jonathan V.; Skutsch, Margaret; Pérez-Salicrup, Diego R.; Salinas-Melgoza, Miguel Angel; Farfán, Michelle (Frontiers in Environmental Science, 2022)
Forest degradation reduces biomass density, contributes to greenhouse gas emissions, and affects biodiversity and natural resources available for local Previous studies have reported that gross emissions from forest degradation might be higher than from deforestation, due to the larger area affected by the first process. The quantification of forest degradation with remote sensing has large uncertainty, mainly because the subtle and gradual changes in forest are challenging to detect. The objective of this work is to map the degraded forests and the most relevant biophysical and socio-economic factors contributing to such degradation in the dry tropics. We mapped the degraded forests by modeling forest biophysical parameters with multi-temporal optical data of Landsat-8 and Sentinel-2 and identified the most relevant biophysical and socio-economic factors that can be associated with forest degradation. We included 3 biophysical variables and 11 socio-economic variables including parceled land and land in ejido property and used multiple linear regression to relate those variables with identified degraded forests. We identified 62878 ha of tropical dry forest in a degraded state, cover 49.91% of the forest area. The most relevant biophysical factor was distance to settlements and the most relevant socio-economic factor was percentage of parceled land property (private land). Both factors were negatively associated with the mapped degraded forests. Since parceled land and land in ejido property are strongly and positively correlated (Pearson’s r = 0.82, p < 0.001), it suggests that ejido property, as a form of land tenure, plays an important role in preventing forest degradation. This experiment presents a possible way to measure and understand degradation which may help finding solutions to slow down forest degradation and promote forest restoration. communities.